Analisi Kinerja Pegawai Bidang Paud Dikmas Pada Dinas Pendidikan Kota Bekasi Tahun 2021 - Anggi Hakiki; Wahidin Septa; Renisya Ayu Utami (Jurnal Ilmu Administrasi Publik, 2022)
The weak performance of employees in the field of PAUD Dikmas of the Bekasi City Education Office is due to the attitudes and behavior of the employees themselves at work. When the author saw the conditions in the field, many employees of the PAUD Dikmas Division of the Bekasi City Education Office violated the rules such as being late for work even though it had been determined that the entry time was 07:30-16:00 WIB and delaying their work because there were outside matters, this would have violated provision. The performance of government officials, especially in the field of PAUD Dikmas at the Bekasi City Education Office, is expected to run optimally. Because it is in accordance with the vision, mission of the program and the design of the main tasks and functions at the Bekasi City Education Office. Mayor's Regulation Number 106 of 2021 states that the Education Office is a regional apparatus that carries out the functions of government affairs in the education sector in the form of a qualitative method. By interviewing six informants, the results of the research were that the Performance Assessment from the Education Office in the field of Early Childhood Education was good, service quality was not responsive, responsiveness was not good, responsibility was not good, and accountability was not good. Obstacles Faced from Dikmas PAUD Sector Budget, human resources, lack of facilities and infrastructure Efforts for Dikmas PAUD Sector conduct work programs and training on human resources, adjusting the budget to the work program created.